The effects of summer learning on social-emotional and behavioral outcomes: A meta-analysis - Kathleen Lynch; Lindsay Lanteri; Lily An; Zid Mancenido; Jennifer Richardson (Social and Emotional Learning: Research, Practice, and Policy)
Recent meta-analyses have documented positive impacts of summer learning programs on literacy and mathematics skills; however, summer learning programs’ effects on SEL outcomes are not well understood. This study comprises a meta-analysis of 36 empirical studies of the effects of summer learning programs for grades PK–12 students. The findings indicated a pooled mean effect size of 0.13 standard deviations on overall SEL outcomes. Positive mean impacts were seen in each of the subdomains examined, including academic mindsets, effort, and attitudes; academic behaviors; and social skills and behavioral adjustment. We also examine potential moderators that may explain variation in these impacts. The findings show that summer learning programs can potentially improve both academic and SEL competencies. We discuss recommendations for future research and implications for practice. Impact statement: Approximately three-quarters of U.S. public schools have administered summer programs in recent years. However, summer learning programs’ effects on SEL outcomes are not well understood. We present a comprehensive meta-analysis of the effects of summer learning programs on PK–12 students’ SEL outcomes.The meta-analysis indicates that summer learning programs can have significant positive effects on students’ SEL outcomes, suggesting that summer programs have the potential to improve both academic and SEL competencies.Researchers and policymakers can use these findings to inform decision-making regarding summer learning programs’ design and implementation, as well as future research that can further strengthen the evidence base.